Mass exodus from Kosovo: How a struggling state loses its citizens - Judith Möllers; Arjola Arapi-Gjini; Sherif Xhema; Thomas Herzfeld (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2015)
A remarkable exodus from Kosovo occurred in the winter 2014/15, raising urgent questions about its underlying drivers and implications for both Kosovo and the destination countries. This policy brief provides a first-hand qualitative snapshot of key migration drivers, as well as insights on some particularities of the phenomenon. We find that the exodus is the result of a struggling Kosovar state, which failed to maintain the enthusiasm and hope of its young nation and turn it into sustainable development. Instead, a lack of perspectives and accumulated frustration about the existing political caste, nepotism and corruption drive out even middle class people. The extent and timing of the migration wave was closely connected with facilitated travel conditions and incentivising rumours that caused a snowball effect. We argue that EU countries will have to react with patience and care in handling incoming migrants. Changes in the asylum and visa regimes are recommended, but a smart timing of measures is important. Ultimately, to prevent a deepening crisis and possible unrest in Kosovo, temporary legal migration opportunities are needed. Within Kosovo, only breaking up existing structures and establishing efficient institutions and functioning social models in their place could allow the country to overcome its economic deadlock.
urn:nbn:de:gbv:3:2-54958
Keywords: 330